The Impact of Bank Indonesia Regulation No. 17/3/2015 on Exchange Rate: Analysis Using Vector Error Correction Model (VECM) - Muhamad Yudi Setiawan; Tanti Novianti; Mukhamad Najib (Binus Business Review, 2021)
The weakening of the Rupiah against the US dollar has encouraged Bank Indonesia to issued Bank Indonesia Regulation (Peraturan Bank Indonesia - PBI) No. 17/3/2015. The research aimed to analyze the factors that affected the Rupiah exchange rate, the effect of PBI No. 17/3/2015 on the movement of the Rupiah exchange rate, and the behavior of exchange rate movement to the shocks on the variables that influenced it. The research applied secondary data, namely monthly data from January 2008 to April 2019 taken from reliable sources such as National Development Planning Agency (Bappenas), Bank Indonesia (BI), and Statistics Indonesia (BPS). It was explanatory research with a quantitative approach. The studied data were processed with the Vector Error Correction Model (VECM) method to identify long and short-term effects. The results of the long-term equation show that export-import has a negative effect on the exchange rate. Similarly, inflation has no significant effect on the exchange rate. Then, the money supply has a significantly negative effect on the exchange rate. However, the interest rate of Bank Indonesia positively affects the exchange rate. Next, the implementation of PBI No. 17/3/2015 has a significant and positive impact on the exchange rate. Last, the crisis condition does not affect the changes in exchange rates.